THE PLACE OF FINANCIAL SECURITY OF THE INDUSTRY IN THE STRUCTURE OF NATIONAL SECURITY - KUNYTSKA-ILIASH, MARTA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The peculiarities of the economy are determined, which testify to the achievement in the state of the necessary level of economic security and a sufficient pace of development of the national economy. Adhering to the existing approaches to the distribution of components of economic security of the state, the priority of financial security is highlighted. Achieving the required level of financial security of the state is due to the sectoral characteristics of the economy and directly to the financial security of the industry. It is established that in the system of relations the financial security of the industry has a direct impact on the financial security of the state and at the same time indirectly determines the level of economic and national security of the state. A number of scientific assumptions concerning the substantive and essential characteristics of the concept of financial security of the industry are highlighted. It is proposed to divide the structural components of the financial security of the industry according to the areas of ensuring the financial interests of the industry, its enterprises and the state. In general, a number of approaches to the substantive and substantive interpretation of the financial security of the industry is characterized by different target orientation (business environment, intra-industry, government regulatory system, the level of globalization trends) in determining the main direction of achieving the desired state. It is proposed to consider the financial security of the industry as a leading component of economic security of the industry system, which characterizes the state of security and the degree of realization of economic interests of its development in the financial sphere. The basic characteristics of the financial security of the industry are the availability of financial resources, the ability to prevent financial risks and threats, stability and stability of the financial and economic condition of the industry, the conditions and opportunities for development and implementation of the financial component of economic potential.